Proximity Effect induced transport Properties between MBE grown (Bi1−xSbx)2Se3 Topological Insulators and Magnetic Insulator CoFe2O4 - Shun-Yu Huang (Nature Portfolio, 2017)
Abstract In this study, we investigate the proximity effect in topological insulator (TI) and magnetic insulator bilayer system. (Bi1−xSbx)2Se3/CoFe2O4 (CFO) heterostructure was fabricated using molecular beam epitaxy and pulsed laser deposition system respectively. As revealed from the magnetoresistance measurement, the weak anti-localization (WAL) is strongly suppressed by proximity effect in (Bi1−xSbx)2Se3/CFO interface. Modified Hikama-Larkin-Nagaoka equation was used to fit the WAL results so that the size of surface state gap can be extracted successfully. The temperature-dependent resistance of the heterostructures at small and large perpendicular magnetic fields were also measured and analyzed. The results indicate that the surface band gap can be induced in TI and continuously enlarged up to 9 T, indicating the gradual alignment of the magnetic moment in CFO under perpendicular magnetic field. The approaches and results accommodated in this work show that CFO can effectively magnetize (Bi1−xSbx)2Se3 and the heterostructures are promising for TI-based spintronic device applications.